Association of genetic polymorphisms in the Fibroblast Growth Factor 23 genes with fibroblast growth factor 23 levels in South African patients with chronic kidney disease - Peddle, Allyson (My University, 2024)
Introduction: It is now understood that FGF23 plays a fundamental role in calcium, phosphate and vitamin D homeostasis and that it can be used as an early biomarker of chronic kidney disease mineral and bone disorders (CKD-MBD). The aim of this study is to investigate genetic polymorphisms in South African patients with CKD-MBD which have been associated with circulating FGF23 levels in Caucasian patients in order to improve our understanding of its role in CKD in a South African population. Methods: Study participants included 293 patients with CKD stage 3-5 and 90 apparently normal participants. Whole blood samples were previously collected and FGF23 levels measured using a sandwich based enzyme-linked immunosorbent assay kit. TaqMan® minor allele groove-binding based allelic discrimination assays were used to genotype the three single nucleotide polymorphisms (rs17216707, rs11741640 and rs4075958). Results: No statistically significant difference was seen in the prevalence of rs4075958 and rs17216707 in participants with CKD compared to controls. There was a significant difference (p=0.03) when comparing the circulating levels of FGF23 in CKD between Black African and Caucasian participants. There was no association between any of the three SNP’s and circulating FGF23 level (all p-values > 0.1). There was a significant association between FGF23 and phosphate levels (p=0.00). Conclusion: The lack of correlation is possibly due to low levels of homozygosity in the minor trait in our sample suggesting other factors play a role in the development of CKD and CKD-MBD. This 4 study has added to existing data supporting the association between hypertension, increased phosphate levels and FGF23.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Internal Medicine to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Genetic polymorphism; Genes; SDG-3: Good health and well-being